СОЦИАЛЬНОЕ ПОЛОЖЕНИЕ СЕЛЬСКОГО НАСЕЛЕНИЯ КАРАКАЛПАКСТАНА В ПОСЛЕВОЕННЫЙ ПЕРИОД - Мадреймов Е. (International Journal of Innovative Technologies in Social Science, 2019)
The article examines some aspects of the social situation of dehkans in the postwar period in Karakalpakstan. During this period, the state takes a number of decisions to increase cotton crops at the expense of grain crops and reduce the homesteads of the rural population. The main source of income of collective farmers was a subsidiary farm, where the main food products were grown. Decline in prices for a number of food and non-food products during 1947-1950. However, food was still unavailable to most, often the shelves of aul shops were empty: some were sold, some were distributed among the executives. Strict control and administration, unfair distribution of goods of mass consumption has led to economic sabotage and migration of the rural population. Collective farmers often opposed administration, but mostly preferred hidden, latent forms of struggle for their own interests, avoiding direct confrontation with the leadership of the collective farm.